Types of Swearing Words Used by The Characters In Birds of Prey - Dhea Syahla; Sri Hartati (LADU: Journal of Languages and Education, 2023)
Background:  Swearing words are not only used in real human life or on social media but are also often found in movies and the use of swearing words in movies must have a specific purpose one of which is to attract the attention of the audience. Purpose: This research aimed at revealing the types of swearing for the characters in the Birds of Prey movie. Design and methods: This research used a qualitative method. The researcher used Andersson and Trudgill’s theory to analyze the data. Results: The result of the research showed that there are four types of swearing; expletive swearing, abusive swearing, humorous swearing, and auxiliary swearing.